2020
DOI: 10.17126/joralres.2020.007
|View full text |Cite
|
Sign up to set email alerts
|

Orofacial space infections, etiology, microbiological susceptibility and surgical management

Abstract: Orofacial infections are considered as one of most common infections and need rapid and adequate treatment as they affect a very delicate region and are associated with serious life-threatening complications. Orofacial infections can be either odontogenic that is with an origin in teeth and associated structures or non-odontogenic, not associated with teeth, can affect facial spaces and spread from one space to another, so a good knowledge about diagnosis and treating these infections is of utmost importance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In contrast to the studies by Ishfaq et al indicated that more prevalence of orofacial infections was found in female patients. 16,17 Oro-facial fascial space infections are relatively uncommon in the paediatric age group. Their occurrence in children is however of importance, and may be a critical sign of social neglect and poverty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the studies by Ishfaq et al indicated that more prevalence of orofacial infections was found in female patients. 16,17 Oro-facial fascial space infections are relatively uncommon in the paediatric age group. Their occurrence in children is however of importance, and may be a critical sign of social neglect and poverty.…”
Section: Discussionmentioning
confidence: 99%
“…24 The 2 nd & 3rd mandibular molar teeth are important origin of infections in deep neck region, as their roots extend to the junction of the mylohyoid muscle & the mandibular corpus adjacent to the submandibular and parapharyngeal spaces, leading to the most frequent involvement of submandibular space by facial space infections. 16 The most frequent presenting complaint found was swelling and pain. In majority of the patients, swelling was present in submandibular region.…”
Section: Discussionmentioning
confidence: 99%
“…The utility of some newer antibiotics, such as new fluoroquinolones and cephalosporins, in treating odontogenic infections and the fact that some older antibiotics are no longer effective can also be inferred from these findings. Contrary to Chunduri et al, who found that amoxicillin was effective against 90% of Gram-positive cocci and 79% of Gram-negative rods, Sulaiman et al study in Iraq found that netilmicin, cefoperazone, and rifampicin had the highest susceptibilities (32,33). In contrast to a previous study's findings, amoxicillin/clavulanic acid resistance was shown to be rather high when compared to resistance to other antibacterial drugs.…”
Section: Discussionmentioning
confidence: 70%